Acquiescent, Defensive and Prosocial Reasons for Employee Silence in a Private Healthcare Organization, Bengaluru - Amrutha P Raju (Sekolah Tinggi Manajemen IPMI, 2023)
Employees are the main pillars of an organization that have individual opinions, ideas and information that helps in workplace and organizational improvement. In modern organizations, employees are not the economic man rather it is essential for them to express emotions, perception, thoughts, experience and attitude regarding their workplace and organization as demanded by the nature of work and its environment. They are the foundation of feedback in dealing with and resolving the complexities. So, with this context the aim of the study was to identify the reasons for employee silence in an organization and impact of the socio-demographic variables on employee silence in a tertiary care hospital. Quantitative data (n=334) were collected from the employees of a tertiary care hospital in Bengaluru, India. Exploratory factor analysis was carried out to find the factors causing employee silence among the employees of the organization and independent sample t-test and One-way ANOVA was performed to find the association between the socio-demographic variables and employee silence. Results from the study have identified four major factors of silence namely; indifference of the management, fear of the management, maintenance of good relationship and prosocial tendency as possible causes of silence. These factors were correlated using Pearson’s correlation to find the association between the identified factors and indifference of the management and fear, maintenance of good relationship and prosocial tendency had a strong positive correlation. Further the study showed there is a relationship between age, education level and work experience with employee silence and it differs with different categories of age, education and years of experience. Since the study is related to healthcare organization more emphasis should be given to the employees as the quality of services delivered would mainly depend on them. The study reveals the need for having a positive interpersonal relationship which gives way for continuous feedback between the management and employees which in turn would lower employee silence in an organization